2020
DOI: 10.3390/atmos11101023
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Snow and Glacier Melt Contribution to Runoff in the Gilgit River Basin via Degree-Day Modelling Approach

Abstract: In contrast to widespread glacier retreat evidenced globally, glaciers in the Karakoram region have exhibited positive mass balances and general glacier stability over the past decade. Snow and glacier meltwater from the Karakoram and the western Himalayas, which supplies the Indus River Basin, provide an essential source of water to more than 215 million people, either directly, as potable water, or indirectly, through hydroelectric generation and irrigation for crops. This study focuses on water resources in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…The contribution of snow to runoff was estimated using various methods and data including the ratio of snowfall to the total precipitation [18], snowfall to total runoff [2,18], SWE to precipitation [19], snowmelt runoff to total runoff [20], degree-day approaches [21][22][23]. Kang et al [24] quantified the contribution of snow to runoff by using the ratio of the spatially averaged peak SWE to runoff and showed that the ratio was in decrease during the period 1949 to 2006 over Fraser River Basin.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of snow to runoff was estimated using various methods and data including the ratio of snowfall to the total precipitation [18], snowfall to total runoff [2,18], SWE to precipitation [19], snowmelt runoff to total runoff [20], degree-day approaches [21][22][23]. Kang et al [24] quantified the contribution of snow to runoff by using the ratio of the spatially averaged peak SWE to runoff and showed that the ratio was in decrease during the period 1949 to 2006 over Fraser River Basin.…”
Section: Introductionmentioning
confidence: 99%
“…It can be said that the negative trend in mean flows affects the dimensions, and hence, the construction cost of the dam can be also considered as a limiting factor for the water quantity withdrawn from the reservoir and storage capacity due to changing climate concerning variability in hydroclimatic trends [67][68][69]. Therefore, it may be concluded that low flows are decreasing annually and seasonally in summer and autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Some hydrological models, such as Snowmelt Runoff Model (SRM) [12,13] and the HBV model [14,15], also use an empirical model to describe the melting process of ice, snow and glacier. These snowmelt runoff simulations also achieved good results [16][17][18][19]. However, the empirical model simulation accuracy decreases with the improvement in time resolution, and it is impossible to describe the spatial variation of snow surface ablation [20].…”
Section: Introductionmentioning
confidence: 96%